FEATURES OF USING MODERN TOOLS OF INNOVATIVE AND CREATIVE TECHNOLOGIES BY RESTAURANT BUSINESS ENTERPRISES - PORSIUROVA, Iryna; BOTIN, Maksym (Herald of Khmelnytskyi National University. Economic sciences, 2024)
The article analyzes the use of innovative and creative technology tools by restaurant business enterprises. It is determined that innovative and creative technologies define a new dimension of restaurant business development. It is outlined that the use of high-tech innovation tools in terms of types of activities will effectively minimize errors and reduce time, attract new customers, forecast demand and optimize the menu, etc. Thus, restaurant business enterprises are actively implementing CRM systems, programs for managing orders, warehousing and personnel, use social networks, paid ads and SEO to promote the restaurant, and the use of Big Data tools and analytical platforms helps to understand customer preferences. Today, the use of QR codes for menus, interactive tables or mobile applications (applications) for self-ordering are common innovative and creative technologies in restaurants. Automated kitchen appliances and monitoring systems ensure efficient use of resources and improve the quality of service, and creative solutions for using VR/AR to create a unique customer experience are important for the development of the Internet of Things and digital marketing. The main directions and prospects for the use of creative innovations in the restaurant business are highlighted, namely, the creation of a unique customer experience, the use of eco-innovations, personalization through technology, the integration of digital technologies, innovations in cooking, cooperation with local communities, automation and robotics, and the development of gamification. It was determined that the problems of implementing innovative and creative technologies are high costs, but their effective use affects the increase in competitiveness, solvency, and profitability through the use of the latest developments; contributes to the expansion of the client base through modern approaches to innovative management; leads to sustainable business development in the context of digitalization. The synergy of the processes of effective management of innovative resources, creative solutions, analytics, and automation ensure stable growth and profitability of restaurant business enterprises.
Keywords: innovative and creative technologies; restaurant business; business process automation; digital marketing; digital platforms and analytics; interactive technologies; Internet of Things; creative solutions